IMPLEMENTATION OF THE JEAN MEEUS ALGORITHM IN CALCULATING NEW MOON AND FULL MOON DATA - Venia, Susan (Al-Hilal: Journal of Islamic Astronomy, 2024)
This research aims to determine the application of Jean Meeus' algorithm in calculating new moon and full moon data. This is a qualitative study using a library approach. The primary source is the book "Astronomical Algorithm" by Jean Meeus, while secondary sources include books, journals, websites, and other information. The research results show that calculating new moon and full moon data using Jean Meeus' algorithm involves several calculation stages: lunation value (k), time in the Julian epoch 2000 (T), M (mean solar anomaly), M' (mean lunar anomaly), F (lunar latitude), and Ω (longitude of the ascending node) in degrees (0⁰ - 360⁰). Then, 14 arguments (components) affecting the planets are calculated in degrees. Next, the average time for moon phases is calculated, considering the influence of lunar and solar ablation and the moon’s light travel time to the observer’s position. Additional correction to the JDE (Julian Day Ephemeris) is required to determine the true phases. Jean Meeus' algorithm is used in the taḥqīqī essential calculation method due to its highly accurate astronomical data corrections for the movements of the Moon and Sun and is part of the heliocentric flow.